Transgenic maize plants with enhanced starch content and yield - Thanh, Nguyen Duc; Luong, Tran Thi; Ninh, Nguyen Thuy; Thu, Nguyen Thi; Huong, Ho Thi; Minh, Vuong Huy (Academia Journal of Biology, 2015)
The demand in food, feed and energy in the word is increasing in every year and exceeds global production. Therefore, the improvement of productivity of maize is of great interest of scientists. One of the approaches for the increase of maize productivity is the enhancement of biosynthesis and accumulation of starch in the seeds. ADP-glucose pyrophosphorylase (AGPase) catalyses the formation of ADP-glucose from ATP and glucose-1-phosphate. And is the key enzyme in regulation of starch accumulation.Genetic modification of this enzyme can enhance the accumulation of the plant that leads to the increase of mass and the seed yield. Shrunken 2 (Sh2) gene coding for large subunits and Brittle2 (Bt2) gene coding for small subunits of ADP-glucose pyrophosphorylase. The transfer of these genes into maize may improve the productivity. In previous works, we have presented the results on successful transfer of Sh2 and Bt2 genes in to several inbred maize lines. This article presents the results on starch content, yield components and yield of the obtained transgenic maize plants. The results showed that the starch content in transgenic plants carried Sh2 transgene was increased from 10.12 to 15.56% comparing to the un-transformed plants, while that of transgenic maize plants with Bt2 transgene was increased from 8.76 to 10.55%. The yield of some transgenic maize lines had increased from 10.41 to 11.16% comparing to un-transformed maize lines. Particularly, the yield of some transgenic plants was increased more than 15%. This is the first research in Vietnam on the improvement of maize yield by genetic engineering. The results obtained will contribute to the study of the role of Sh2 and Bt2 gene in starch biosynthesis and accumulation in maize.